CINTA SEBAGAI RELIGIOUS PEACE BUILDING (Perspektif Muhammad Fethullah Gülen) - Ahmad Kholil (UIN Sunan Kalijaga Yogyakarta, 2014)
Sociologically, religion has a double function. On the one hand, religion can be a factor of social cohesion and harmony creation, but on the other hand it can also be a factor religious disharmony between people of different religions. This paper examines the views of Fethullah Gülen on the social function of religion that is based on love and peace. Differences of religion, according to him, is a consequence of the choice of each human being in order to establish the absolute truth based on how they believe. Therefore, differences in religion is not something scar y or even harmful for social life, as long as people are able to live in the light of love and peace.